Life history of Amblyseius compositus Denmark & Muma preying on Brevipalpus phoenicis (Geijskes) (Acari: Phytoseiidae, Tenuipalpidae) - Reis, Paulo Rebelles; Teodoro, Adenir Vieira; Pedro Neto, Marçal (Coffee Science - ISSN 1984-3909)
Predatory mites belonging to the Phytoseiidae family, among them Amblyseius compositus Denmark & Muma, 1973, have been found in coffee plants (Coffea arabica L.) and adjacent forest fragments in of Lavras, MG, Brazil, associated to the Brevipalpus phoenicis (Geijskes, 1939) (Tenuipalpidae), Which is the vector of the coffee ring spot virus. The biological aspects, fertility life table, predatory activity, and functional and numeric responses, in function of the prey B. phoenicis density, were studied in laboratory at 25 ± 2oC, 70 ± 10% of RH and 14 hours of photophase. A longevity of 48 days was verified for the adult females. The innate capacity of the predator population’s growth (rm) was 0.119 females/female/day and the mean generation time (T) was 27.9 days. The population doubled every 5.8 days. In bioassays, 20 B. phoenicis mites per coffee leaf arena (3-cm diameter) were offered separately to a specimen of each phase of the predatory mite. It was verified that the female was the most efficient consumer in all development phases of the prey mite, although the nymph also presented good predation. To analyze functional and numeric responses, the prey was offered in densities from 0.14 to 42.3 immature B. phoenicis per cm2 of arena, the preferred phases for predation. The predatory activity and the oviposition of A. compositus increased according to the increase of prey density, in a positive and highly significant correlation. The regression analysis suggests a type II functional response with maximum predation between 30 and 35 B. phoenicis/cm2/female.